(untitled) (Teología, 2018)
Poetry is meticulous: it celebrates every little gift that is constantly offered; it rescues it, it mentions it. Poetry is also magnanimous: it sings the secret bonds which, in each and every thing, weave them together in one single offering, in mutual unity and reference. Poetry is wise: it asks and knows Being in all its depth, in the springs of all that is celebrated and sang by the poetic word, it has affinity with it, connaturality. Lastly, poetry is hopeful and open. She knows her limits, but just as a threshold: it waits and yearns for the Word, ineffable, in which everything, even Being, has its consistency. Poetry makes silence and listens, summons, yearns for the Gift that come from on high and incarnates. This is the aim of the great poet, the elder brother. Among argentines, Jorge Luis Borges is perhaps the best in adapting language to reach this place, the highest, making us come closer to the mystery, while being at the same time witnesses to the distance. These are the matters, at bottom the one matter, poetry is made of. From what is tiniest and most fragile to what is greatest and definitive, expressed and incarnated. In words of Von Balthasar: the resurrection of the flesh proves poets are right.